2011
DOI: 10.1103/physrevd.83.103514
|View full text |Cite
|
Sign up to set email alerts
|

Integrating out astrophysical uncertainties

Abstract: Underground searches for dark matter involve a complicated interplay of particle physics, nuclear physics, atomic physics and astrophysics. We attempt to remove the uncertainties associated with astrophysics by developing the means to map the observed signal in one experiment directly into a predicted rate at another. We argue that it is possible to make experimental comparisons that are completely free of astrophysical uncertainties by focusing on integral quantities, such as g(vmin) = v min dv f (v)/v and v … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
232
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(233 citation statements)
references
References 58 publications
1
232
0
Order By: Relevance
“…For example, the direct detection limits rely on an assumption about the local dark matter density and velocity distributions, the latter of which is expected to vary from the standard assumptions used in the experimental results [59][60][61][62][63][64][65]. While it is possible to some degree to disentangle the astrophysical uncertainties to place limits on the fundamental parameters [66][67][68][69][70][71], we cannot lose sight of the assumptions that went into the analysis. Similarly, the parameters that are required to obtain a thermal relic abundance can be changed significantly if additional particles (beyond the minimal set in our benchmark simplified models) are present in the spectrum, or if the flavor-universal assumption for the coupling g v is lifted.…”
Section: Non-collider Boundsmentioning
confidence: 99%
“…For example, the direct detection limits rely on an assumption about the local dark matter density and velocity distributions, the latter of which is expected to vary from the standard assumptions used in the experimental results [59][60][61][62][63][64][65]. While it is possible to some degree to disentangle the astrophysical uncertainties to place limits on the fundamental parameters [66][67][68][69][70][71], we cannot lose sight of the assumptions that went into the analysis. Similarly, the parameters that are required to obtain a thermal relic abundance can be changed significantly if additional particles (beyond the minimal set in our benchmark simplified models) are present in the spectrum, or if the flavor-universal assumption for the coupling g v is lifted.…”
Section: Non-collider Boundsmentioning
confidence: 99%
“…On the assumption that there is no dark form factor, the event distributions (once we have compensated for the different target nuclei) with respect to v min should be the same for each of the experiments [26][27][28][29][30][31] -any disagreement indicates the presence of some extra effect. For a dark form factor, since q(v min ) = 2µ XN v min , changing µ XN by changing m N will change the range of F X (q) that we sample (significantly so if the DM mass is larger than those of the SM target nuclei).…”
Section: Jhep07(2015)133mentioning
confidence: 99%
“…Models of the type considered here retain the appeal of the thermal relic hypothesis while remaining experimentally verifiable. We have furthermore demonstrated that in this class of indirect annihilation searches, all astrophysical uncertainties can be "integrated out" [40] and experimental sensitivities can be directly compared.…”
mentioning
confidence: 99%
“…The kinematics of scattering in the non-relativistic case are controlled by the minimum DM particle velocity, v min (E R ), required to produce a nuclear recoil of energy E R . In the absence of unknown form factors, all experimental data can be mapped into v minspace at each DM mass and compared without specifying the nature of the astrophysical distribution or density of DM [39,40]. These "halo-independent" methods have received significant attention [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
mentioning
confidence: 99%
See 1 more Smart Citation